Seed germination of marmelo do cerrado under inoculation of bacillus licheniformis and exposure to sewage sludge - da Silva Santos, Jaqueline; da Silva Pontes, Montcharles; Kissi, Yaovi Abel; Cassol, Aline Lazzaretti; Batistote, Margareth [UNESP]; Santiago, Etenaldo Felipe [UNESP] (Fronteiras: Journal of Social, Technological and Environmental Science, 2020)
Sewage sludge (LE) is the final waste resulting from sewage treatment, it can promote benefits to vegetables due to its nutritional load. On the other hand, the imbalance of its nutrients can cause phytotoxicity. Therefore, the use of bioremediation bacteria can be an alternative to mitigate the toxicity of this residue and enable its use as a substrate component for the production of seedlings of native species. In that study, germinative responses from seeds of Alibertia edulis (L.C. Rich) A.C. Rich. without inoculum (SI) and inoculated with Bacillus licheniformis (CI) and submitted to different doses of LE (0%, 25%, 50%, 75%, and 100%) were evaluated. In order to assess whether the toxic effects of LE could be mitigated by the inoculated bacteria. The results obtained show a higher germinative percentage (% G) for 0% LE SI. However, the G% observed in seeds IC suggests better germinative performance to all LE concentrations. Thus, it is concluded that the inoculation of B. licheniformis in A. edulis seeds reduced the effects of stress caused by LE and promoted an increase in the %G, indicating that the inoculated bacteria acted as a efficient bioremediation processes of toxic compounds present in LE, mitigating toxicity of this residue.
Germinação De Sementes De Marmelo Do Cerrado Sob Inoculação De Bacillus Licheniformis E Exposição A Lodo De Esgoto.
Keywords: Alibertia edulis; Bacterial inoculation; Bioremediation; Seed; Sewage sludge